PENYULUHAN EDUKASI PENGGOLONGAN OBAT DI SD NEGERI 1 SRENGSEM - Ade Maria Ulfa; Charindra Otista Kafuri; Inggrid Virzinia Subroto; Jeny Pupita Sari; Roz Romaeda (Jurnal Pengabdian Farmasi Malahayati (JPFM), 2023)
ABSTRACT Students at SDN 1 Srengsem Bandar Lampung have a lack of knowledge about drugs and their classification. Based on the information obtained, the principal, teachers and students of SD Negeri 1 Srengsem Bandar Lampung have never received information about the classification of drugs and the dangers of consuming drugs indiscriminately, so it is necessary to disseminate information about the classification of drugs and the dangers of consuming drugs indiscriminately. The methods used for students in this activity are lectures, questions and answers, giving posters and filling out questionnaires for the material that has been delivered. This questionnaire was conducted with the aim of finding out how much the children's understanding of the material that has been delivered. The outreach activities on the classification of these drugs went smoothly. The students who attended were very enthusiastic and enthusiastic in listening to explanations and actively asked questions regarding the classification of drugs based on their types and the dangers of consuming drugs indiscriminately. This counseling increases participants' understanding of the classification of drugs properly and correctly, it is hoped that students can apply the knowledge that has been obtained in the family environment and the surrounding community. Keywords: Drugs, Classification, Students, Health, Society  ABSTRAK Siswa-siswi di SDN 1 Srengsem Bandar Lampung  belum memahami pengetahuan tentang obat dan penggolongannya berdasarkan informasi yang diperoleh dari kepala sekolah dan guru SD Negeri 1 Srengsem Bandar Lampung sehingga perlu dilakukan sosialisasi tentang penggolongan obat dan bahaya mengkonsumsi obat tidak sesuai aturan pakai. Metode yang digunakan adalah ceramah, tanya jawab, menggunakan leaflet dan mengisi kuisioner materi yang telah disampaikan. Tujuan penyuluhan ini untuk mengetahui seberapa besar pemahaman anak-anak terkait materi yang telah disampaikan. Kegiatan penyuluhan tentang penggolongan obat ini berjalan dengan lancar. Para siswa-siswi yang hadir sangat antusias bersemangat dalam mendengarkan penjelasan dan aktif bertanya terkait penggolongan obat berdasarkan jenisnya dan bahaya mengkonsumsi obat sembarangan. Penyuluhan ini meningkatkan pemahaman peserta tentang penggolongan obat dengan baik dan benar dari 61 % mejadi 95%. diharapkan siswa- siswi dapat menerapkan pengetahuan yang telah diperoleh dalam lingkungan keluarga dan masyarakat sekitar.Kata Kunci : Obat, Penggolongan, Siswa, Kesehatan, Masyarakat